Hybrid sustainability dilemma theory: A microfoundational explanation for sustainability cooperation failures - Silvestre, W. J. (Business Strategy and the Environment, 2026)
This article introduces the hybrid sustainability dilemma theory (HSDT), a multilevel microfoundational framework that explains why organisations frequently adopt noncooperative strategies in sustainability contexts, even when collective outcomes would be superior. Drawing on game theory, behavioural strategy and organisational paradox research, HSDT conceptualises sustainability decisions as repeated cooperation dilemmas shaped by hybrid trade-off intensity (HTI): the structural tension arising from competing economic, social and environmental objectives assessed through incompatible metrics and divergent temporal horizons. The theory proposes that HTI increases the likelihood of defection through cognitive microfoundations including temporal discounting, loss aversion and competitive framing. Integrative sustainable intelligence (ISI) moderates this relationship, attenuating the negative effect of trade-off intensity on cooperation when distributed across organisational units and supported by collaborative governance. Strategic cooperation, in turn, mediates the pathway from ISI to organisational resilience, while organisational interdependence and institutional complexity function as amplifying boundary conditions. Four theoretical propositions formalise these relationships, specifying directionality, contingent conditions and nonlinear effects. The framework operates across three analytical levels: individual cognition, organisational coordination and institutional context and offers a simplified empirical model testable through multilevel structural equation modeling. For managers, HSDT provides a diagnostic lens for identifying the structural and cognitive conditions that generate cooperation failures and for designing incentive systems that support sustainable collective action.